Baseline and 2-year differences in spinal symptoms and spinal and hip mobility in early axial spondyloarthritis and non-axial spondyloarthritis chronic back pain patients - Sofia Ramiro; Désirée van der Heijde; Roberta Ramonda; Floris A van Gaalen; Mary Lucy Marques; Sofia Exarchou; Miranda van Lunteren; Camilla Fongen; Marleen van de Sande; Ana Bento da Silva (RMD Open)
Objective To compare spinal symptoms and spinal/hip mobility at baseline and 2 years in early axial spondyloarthritis (axSpA) and non-axSpA chronic back pain (BP) patients.Methods Baseline and 2 years data of the SPondyloarthritis Caught Early cohort were analysed. Outcomes assessed: overall BP, BP at night, morning stiffness (MS) intensity, MS duration, occiput-to-wall distance (OWD), cervical rotation, chest expansion, lateral spinal flexion (LSF), modified Schober test (mSchober), intermalleolar distance (IMD) and Bath Ankylosing Spondylitis Metrology Index (BASMI). Linear or zero-inflated negative binomial regression was used to compare 2 years outcomes between groups (adjusting for baseline value, sex, age and use of non-steroidal anti-inflammatory drugs).Results There were 294 axSpA and 123 non-axSpA patients (mean symptom duration: 13 months). At baseline, non-axSpA patients had worse symptoms and mobility, except OWD (eg, mean(SD): BP at night 3.6 (2.9) axSpA vs 4.6 (2.7) non-axSpA; OWD 0.5 (1.2) vs 0.1 (0.7)). After 2 years, all symptoms and cervical rotation significantly improved in both groups, but LSF and mSchober only in axSpA. In multivariable analyses, axSpA was associated with larger improvements in BP at night (β (95% CI): −0.85 (−1.47; −0.23)), mSchober (0.26 (0.03; 0.50)), IMD (4.86 (1.93; 7.80)) and BASMI (−0.24 (−0.41; −0.08)), and with lower likelihood of a normal OWD (OR (95% CI): 0.09 (0.01; 0.83)).Conclusion Over 2 years, all spinal symptoms and some mobility measures improved in both groups, but impairments remained prevalent (particularly in non-axSpA). Nevertheless, axSpA was associated with larger improvements in BP at night, mSchober, IMD and BASMI, but with more OWD impairment.